Interactions between crude drug extracts used in Japanese traditional Kampo medicines and organic anion-transporting polypeptide 2B1. (25th March 2018) - Iijima, Rie; Watanabe, Tomoki; Ishiuchi, Kan'ichiro; Matsumoto, Takashi; Watanabe, Junko; Makino, Toshiaki
Abstract: Ethnopharmacological relevance: The use of herbal medicines has become popular worldwide, and the information on drug interactions between herbal medicines and chemical drugs is needed. Aim of the study: We screened the inhibitory effects of crude drugs used in Kampo medicines used in Japan on organic anion-transporting polypeptide (OATP) 2B1 to predict potential interactions between Kampo medicines and chemical drugs used together. Materials and methods: We chose 98 kinds of crude drugs frequently used as ingredients of Kampo formulations in Japan and prepared their boiling water extracts. We then screened their inhibitory effects on OATP2B1 by measuring the uptake of estrone 3-sulphate (E3S) by HEK293 cells stably expressing OATP2B1. Results: At the concentration of 100 µg/ml, the extracts prepared from 12 kinds of crude drugs, Scuteralliae Radix, Arecae Semen, Aurantii Fructus Immaturus, Perillae Herba, Panacis Japonici Rhizoma, Moutan Cortex, Polygalae Radix, Rhei Rhizoma, Cannabis Fructus, Chrysanthemi Flos, Eriobotryae Folium, and Querci Cortex, suppressed the function of OATP2B1 by less than 20%. The extract of bofutsushosan, a representative Kampo formulation, inhibited OATP2B1 function with sufficient levels to suppress absorption of OATP2B1 substrates in clinics. We further evaluated the inhibitory effects of several ingredients containing Rhei Rhizoma, Perillae Herba, and Moutan Cortex on OATP2B1. Conclusions: Because of crude drugs used in Kampo medicines might suppress absorption of OATP2B1 substrates, these results may contribute to the safe and effective use of Kampo medicine in clinics. A list of abbreviations: EC, (−)-epicatechin; ECG, epicatechin gallate; EGC, epigallocatechin; EGCG, Epigallocatechin gallate; FBS, fetal bovine serum; grapefruit juice; HEK293, Human embryonic kidney; IC50, The half inhibitory concentration; OATP, organic anion-transporting polypeptide; β-PGG, penta- O -galloyl-β-D -glucose; t.i.d, 3 times a day Grpahical abstract: